2012
DOI: 10.1002/aur.239
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Autism and Other Pervasive Developmental Disorders

Abstract: We provide a systematic review of epidemiological surveys of autistic disorder and pervasive developmental disorders (PDDs) worldwide. A secondary aim was to consider the possible impact of geographic, cultural/ethnic, and socioeconomic factors on prevalence estimates and on clinical presentation of PDD. Based on the evidence reviewed, the median of prevalence estimates of autism spectrum disorders was 62/10 000. While existing estimates are variable, the evidence reviewed does not support differences in PDD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

47
1,477
5
77

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,151 publications
(1,606 citation statements)
references
References 71 publications
47
1,477
5
77
Order By: Relevance
“…Recent epidemiological studies on global prevalence of autism spectrum disorder (ASD) revealed that the estimate increased over time with a median prevalence of 62/10,000, indicating that worldwide one in 160 children has ASD (Elsabbagh et al 2012;World Health Organization 2017). These children and their families risk facing social stigma, isolation, and discrimination (World Health Organization 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies on global prevalence of autism spectrum disorder (ASD) revealed that the estimate increased over time with a median prevalence of 62/10,000, indicating that worldwide one in 160 children has ASD (Elsabbagh et al 2012;World Health Organization 2017). These children and their families risk facing social stigma, isolation, and discrimination (World Health Organization 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1 Current prevalence estimates of ASD range from 6.2 to 14.7 per 1,000 children, with 30 to 40% in the intellectually disabled range. 2,3 Young children with ASD consistently show deficits in activities of daily living (toileting, dressing, use of utensils and play skills). Adaptive functioning in children with ASD as measured on the Vineland Adaptive Behavior Scales is lower than predicted by IQ.…”
Section: Introductionmentioning
confidence: 99%
“…Autism is generally more frequent in societies occupying higher latitudes, with northern European descent populations have higher rates of autism than those of southern European descent (Elsabbagh et al 2012). In turn, autism rates are notably higher amongst non-Hispanic than Hispanic communities in the US (Palmer et al 2010).…”
Section: Modern Patterns Of Diagnosismentioning
confidence: 99%